The Patterns of Religious Conflict In Indonesia (1990-2008) - Samsu Rizal Panggabean; Rudi Harisyah Alam; Ihsan Ali-Fauzi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
The objectives of this study were to identify the patterns of religious conflicts in Indonesia and to identify policies taken by the security forces, in particular the police. In looking at patterns of religious conflicts, we sought to understand the type, level, development, spread, actors, and the background issues behind the conflicts. In addition, we look at the presence of security forces at the time of incidents, elements of security forces involved in the operations, and what security measures were taken. The analysis of this study focuses on religious conflicts. It is possible that one news item covered or reported more than one incidence.DOI: 10.15408/sdi.v17i2.461